A general protocol for π-conjugated molecule-based micro/nanospheres: artificial supramolecular antenna in terms of heterogeneous photocatalysis1. Issue 96 (17th October 2015) - Zhang, Xiao; Wang, Yanping; Chen, Penglei; Guo, Peipei; Liu, Minghua
<x xml:space="preserve">Abstract</x> An oil-in-water-mediated surfactant-assisted assembly is initiated as a general method for π-conjugated molecules-based micro/nanospheres, supramolecular antenna with regard to heterogeneous photocatalysis has been realized using porphyrin spheres.